Exploring the impact of left ventricular diastolic dysfunction on postoperative cardiac surgery outcomes, with a focus on sex disparities: a comprehensive literature review - Ludden, T.; Alberts, T. A. M.; Breel, J. S.; de Klerk, E. S.; Javaid, S. K.; Boekholdt, S. M.; Hermanides, J.; Hermanns, H.; Eberl, S. (Frontiers in Anesthesiology, 2023)
Introduction Left ventricular diastolic dysfunction (LVDD) is known to cause worse outcomes after cardiac surgery. Females have twice the risk of developing LVDD compared with males. The aim of this literature review was to evaluate the association between LVDD and early (≤30 days) outcomes after cardiac surgery, including sex disparities. Methods We identified 454 studies in Medline and Embase, of which 19 were included. Articles were assessed for inclusion of female patients with LVDD, ≥50 years of age undergoing cardiac surgery (on or off-pump) or transcatheter aortic valve replacement. The primary outcome was early postoperative mortality. Secondary outcomes were early postoperative complications, ICU length of stay (ICULOS), hospital length of stay (HLOS), and other sex-related postoperative outcomes. Results In patients with LVDD, the majority of studies showed that higher LVDD grades correlate with higher early postoperative mortality. In patients with LVDD, who underwent on-pump cardiac surgery, female sex was significantly associated with higher LVDD grades and baseline E/e' ratios. Females with LVDD, were associated with prolonged HLOS after off-pump coronary artery bypass grafting (CABG). In combined cardiac surgery, a twofold increased risk of prolonged HLOS and increased ICULOS was reported. Furthermore, increased left ventricular end-diastolic filling pressure, an increased need for postoperative inotropic support, and difficult separation from cardiopulmonary bypass were observed. Discussion Despite the limited number of studies focusing on sex differences, females with LVDD appear to have worse early outcomes after cardiac surgery compared to men with LVDD. Future research will need to identify sex-specific risk factors and target treatment optimization.